Factors related to caring behavior of nurses in the internal care room - Rusli Rusli; Anggi Pratiwi; Sitti Zakiyyah Putri; Trimaya Cahya Mulat; Nur Andani (Edukasi Ilmiah Indonesia, 2023)
Caring is a crucial aspect of healthcare, especially in the context of care in the internal space, where patients often experience complex health conditions that require special attention. This study investigates factors related to nurses' caring behaviour in the internal care room. roomThis type of research uses quantitative types with analytical descriptive research design through a cross-sectional approach with total sampling techniques. The results of the chi-square statistical test obtained motivation p 0.219, reward p 0.020, and length of work p: 0.008It can be concluded that there is a relationship between reward and length of work with the caring behaviour of nurses in the internal care room. Appreciation and length of work influence the caring behaviour of nurses in the internal care room. Length of work provides extensive experience and knowledge, while rewards increase nurses' motivation and job satisfaction. Combining these two factors can create a caring environment and positively impact patients in the internal care room.